MANAJEMEN NYERI PADA NY. I DENGAN HEPATOMA (HEPATOCELLULAR CARCINOMA) DI RUANG RAWAT INAP PENYAKIT DALAM RSUD KABUPATEN SUMEDANG: STUDI KASUS - Khoerunnissa, Khoerunnissa; Fitri, Siti Ulfah Rifa’atul; Harun, Hasniatisari (SENTRI: Jurnal Riset Ilmiah, 2023)
Hepatoma is the type of cancer with the fourth highest incidence in Indonesia in 2020. The most common manifestation of Hepatoma patients is pain, 9 out of 10 patients complain of pain with an average pain scale of > 8 (0 – 10 NRS). One of the pain management that can reduce pain level is a combination of pharmacological and non-pharmacological therapy. The purpose of this case study is to provide nursing care for pain management in Hepatoma patients through collaborative interventions providing pharmacological therapy combined with non-pharmacological therapy using the case study approach method through the nursing process. Participants in this case study were one patient who was diagnosed with Hepatoma with a nursing diagnosis of Acute Pain. The instrument used to measure the pain scale is the Numeric Rating Scale (NRS). Intervention was given in collaboration with the administration of opioid therapy combined with non-pharmacological therapy of slow deep pursed lip breathing 3 sessions per day for 3 x 24 hours. The evaluation results showed that before the intervention was given the pain level was on a scale of 9 and after the combined intervention the pain level decreased to a scale of 1. The conclusion of this case study is that a combination of pharmacological and non-pharmacological therapy can significantly reduce pain levels in patients.